(untitled) (Stamford Journal of Microbiology, 2025)
The gut microbiome is the large community of bacteria that inhabits the human gastrointestinal system. They contribute significantly to our overall health. These microorganisms have a significant impact on brain function and behavior through the gut-brain axis. Our immune system is also influenced by these microorganisms. This review focuses on developing studies that connect gut microbial activity and composition to mental health outcomes, such as anxiety and depression. The microbiota can influence brain signaling by producing neuroactive substances such as serotonin, dopamine, and gamma-aminobutyric acid (GABA). The hypothalamic-pituitary-adrenal (HPA) axis and immunological responses are also regulated by them. Microbial imbalance has been associated with an increased risk of mental disease, reduced neurogenesis, and inflammation. Dietary factors and microbial exposure at the developing stage also have an impact on the gut microbiota’s influence on emotional and cognitive development. The microbiome-based therapies, such as dietary modifications, for the prevention and treatment of mental disorders can be developed by utilizing these pathways. Stam. J. Microbiol. 2025;15(1):6-12